Histopathological and molecular characteristics of IDH-wildtype glioblastoma without contrast enhancement: implications for clinical outcomes - Foltyn-Dumitru, Martha; Banan, Rouzbeh; Schell, Marianne; Mahmutoglu, Mustafa A.; Keßler, Tobias; Wick, Wolfgang; Brugnara, Gianluca; Bendszus, Martin; Sahm, Felix; Vollmuth, Philipp (Neuro-Oncology, 2025)
Glioblastoma (GB) heterogeneity poses substantial challenges for diagnosis and treatment. Isocitrate dehydrogenase (IDH)-wildtype GB may lack contrast enhancement on MRI and exhibit a “low-grade radiologic appearance” (non-contrast-enhancing [CE] GB), a phenomenon with unclear clinical implications. This study investigates the histopathological and molecular differences and survival outcomes between CE and non-CE GB.This retrospective study at Heidelberg University Hospital analyzed 457 IDH-wildtype GB cases (09/2009-01/2021). Contrast enhancement on preoperative MRI was volumetrically assessed, classifying tumors as non-CE/CE GB using a 1 cm³ cutoff. Molecular and histopathological features, including microvascular proliferation, necrosis, and overall survival (OS), were compared between the groups.Of the initial cohort, 352 (77%) patients met the inclusion criteria, with 44 (12.5%) non-CE and 308 (87.5%) CE GB. The histopathological assessment revealed that non-CE GB was less likely to present traditional hallmarks of GB, such as microvascular proliferation (39% vs. 94%) and necrosis (25% vs. 92%) (P < .001). In the non-CE group, 24 patients (55%) were diagnosed as molecular GB, compared to only 8 patients (3%) in the CE group (P < .001). A significant difference was observed in Ki-67 levels, with non-CE GBs having a lower mean Ki-67 index of 18% ± 12% compared to 26% ± 13% in CE tumors (P < .001). The median OS was 27.2 months (95% CI, 19.8-NA) for non-CE and 14.7 months (95% CI, 13.2-17.1) for CE GB (P = .0049).IDH-wildtype GBs without contrast enhancement are often diagnosed based on molecular criteria due to less frequent histopathological hallmarks and are associated with prolonged OS.